The introduction of broker anonymity on the New Zealand Exchange - Poskitt, Russell; Marsden, A.; Nguyen, N.; Shen, J. (Emerald Group Publishing, 2011)
Purpose – The purpose of this paper is to examine the impact of the introduction of anonymous trading on the liquidity of New Zealand Stock Exchange (NZX)-listed stocks. Design/methodology/approach – The paper examines the impact of the switch to anonymous trading on effective spreads and adverse selection costs using both univariate and multivariate approaches and data spanning a 240-day event window period. The paper also compares the NZX's share of trading in cross-listed stocks before and after the switch to anonymous trading to determine if the change in market architecture improved the NZX's competitiveness vis-à-vis the Australian Stock Exchange (ASX). Findings – The paper finds that effective spreads and adverse selection costs increased following the switch to anonymous trading across the broad range of NZX50 stocks, consistent with an increase in information risk in the post-event period. However, the paper also finds that the switch to anonymous trading improved the NZX's market share in trading in cross-listed stocks vis-à-vis the ASX. Originality/value – The results show that market liquidity deteriorates in a more opaque environment due to the greater information risk facing investors. This is in sharp contrast to prior research, which reports that similar changes in pre-trade transparency on other exchanges have improved market liquidity. The results suggest that although institutional investors and the NZX itself might well have benefited from the switch to anonymous trading, liquidity demanders face higher transaction costs as a result.